Design and combination of magnetic ionic liquids and hydrophobic deep eutectic solvents for safer extraction of titanium: physicochemical properties and toxicity studies. Issue 19 (7th September 2022) - Zhu, Keyu; Wei, Qifeng; Liu, Kang; Li, Huaquan; Ren, Xiulian
Abstract : Three magnetic ionic liquids (MILs) and five hydrophobic deep eutectic solvents (HDESs) were designed and combined for safer extraction of titanium from an HCl leachate of ilmenite for the first time. Abstract : The existing methods for obtaining titanium are harmful as toxic organic solvents must be used. In this paper, three magnetic ionic liquids (MILs) and five hydrophobic deep eutectic solvents (HDESs) were designed and combined for safer extraction of titanium from an HCl leachate of ilmenite (HLI). First, the physicochemical properties including density, viscosity, water content, total organic carbon, and appearance and extraction performance including efficiency, selectivity and reusability of the designed solvents were thoroughly analyzed and compared. Second, the most suitable cation to form MILs for the removal of iron and the best HDES for the extraction of titanium were defined based on sustainable chemistry metrics. The purity of the obtained titanium solution could reach 99.87% after the combined use of the selected MIL and HDES. Finally, toxicity studies on the reagents applied were performed and compared with existing methods.